PENERAPAN KONSEP WATER SENSITIVE URBAN DESIGN UNTUK MEWUJUDKAN PERMUKIMAN PESISIR KOTA PEKALONGAN YANG TANGGUH - Santy Paulla Dewi; Retno Widjajanti; Novia Sari Ristianti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2022)
Coastal settlements are areas with a high level of vulnerability, both in terms of floods, tidal waves, land subsidence, and threats from climate change. Settlements in the North Pekalongan District are part of the coastal area, which is also struggling with flooding and tidal problems. Current efforts by the government tend to be responsive to current problems, and there are no adaptive efforts that look at long-term impacts. Therefore, the purpose of this research is to develop the application of the Water Sensitive Urban Design concept to realize resilient coastal settlements. The Water Sensitive Urban Design concept is one of the efforts that are based on coastal characteristics. The research method used quantitative descriptive, to identify the characteristics of the settlement and formulate design directions for the application of the Water Sensitive Urban Design concept. The results of this study showed that the application of the concept of Water Sensitive Urban Design are structuring river borders on the Loji River, providing air storage ponds downstream of the river, and installing rainwater harvesting systems. Keywords: Water sensitive urban design, settlements, coastal area